High-Intensity Interval Training Improves Cardiac Function by miR-206 Dependent HSP60 Induction in Diabetic Rats - Delfan, Maryam; Amadeh Juybari, Raheleh; Gorgani-Firuzjaee, Sattar; Høiriis Nielsen, Jens; Delfan, Neda; Laher, Ismail; Saeidi, Ayoub; Granacher, Urs; Zouhal, Hassane (Frontiers in Cardiovascular Medicine, 2022)
Objective A role for microRNAs is implicated in several biological and pathological processes. We investigated the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on molecular markers of diabetic cardiomyopathy in rats. Methods Eighteen male Wistar rats (260 ± 10 g; aged 8 weeks) with streptozotocin (STZ)-induced type 1 diabetes mellitus (55 mg/kg, IP) were randomly allocated to three groups: control, MICT, and HIIT. The two different training protocols were performed 5 days each week for 5 weeks. Cardiac performance (end-systolic and end-diastolic dimensions, ejection fraction), the expression of miR-206, HSP60, and markers of apoptosis (cleaved PARP and cytochrome C) were determined at the end of the exercise interventions. Results Both exercise interventions (HIIT and MICT) decreased blood glucose levels and improved cardiac performance, with greater changes in the HIIT group (p < 0.001, η2: 0.909). While the expressions of miR-206 and apoptotic markers decreased in both training protocols (p < 0.001, η2: 0.967), HIIT caused greater reductions in apoptotic markers and produced a 20% greater reduction in miR-206 compared with the MICT protocol (p < 0.001). Furthermore, both training protocols enhanced the expression of HSP60 (p < 0.001, η2: 0.976), with a nearly 50% greater increase in the HIIT group compared with MICT. Conclusions Our results indicate that both exercise protocols, HIIT and MICT, have the potential to reduce diabetic cardiomyopathy by modifying the expression of miR-206 and its downstream targets of apoptosis. It seems however that HIIT is even more effective than MICT to modulate these molecular markers.